Diálogos possíveis entre educação patrimonial e o ensino da geografia. - Lehr, Manoela Moroskoski (2024)
This dissertation, entitled "Possible dialogues between Heritage Education and the Teaching of Geography", is the result of research linked to the Research Group: Representações, Espaços, Tempos e Linguagens em Experiências Educativas – RETLEE, to the Postgraduate Program in Education - Master's Degree - Area of Concentration: Education, Line of Research: Culture, Educational Processes and Teacher Training, of the Universidade Estadual do Oeste do Paraná (Unioeste), Campus of Francisco Beltrão. In it, we contextualize the difficulty felt by the Geography teacher-author in bringing the teaching of this science closer to Heritage Education. The aim was to identify and analyze the interactions between these areas of knowledge. The research followed the path of participant methodology, which involved visits to five museums, where data was collected and analyzed according to the objectives set, which included evaluating the potential of these places for the formation of geographical knowledge. The museums that took part in this research are located in South America; other criteria listed were: proximity to Brazil, to make it easier to get around, and access, which was the offer of free admission. The geographical concepts inherent to heritage in space time were evaluated, based on Milton Santos. The results indicate that Heritage Education plays a fundamental role in preserving and disseminating society's cultural heritage. We can see that the mediation promoted by/within the school community is primarily responsible for working with concepts linked to heritage, as well as understanding legislation, since it broadens the subjects' understanding of history and culture. The intersection between heritage education and geographical concepts strengthens cultural identity and the formation of collective memory. We emphasize the importance of mediation for understanding museum objects-artefacts, for the connection between museums, heritage, Heritage Education and Geography.